2018
DOI: 10.1016/j.mehy.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Should whole body cryotherapy sessions be differentiated between women and men? A preliminary study on the role of the body thermal resistance

Abstract: The aim of this study was to investigate how body thermal resistance between sexes evolves over time in the recovery period after a WBC session and to show how this parameter should be considered as a key parameter in WBC protocols. Eighteen healthy participants volunteered for the study (10 males and 8 females). Temperature (core and skin) were recorded pre- and post (immediately and every 5 min until 35 min post) exposure to a single bout of WBC (30 s at -60 °C, 150 s at -110 °C). From both core and skin tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…There are differences in metabolic reactions to the cold between lean and over-weight people. A higher concentration of body fat percentage in women than in men determines the higher females inner thermal resistance [62]. Since only 2 women participated in our study, we are unable to infer any differences with regard to the sex of the participants.…”
Section: Resultsmentioning
confidence: 84%
“…There are differences in metabolic reactions to the cold between lean and over-weight people. A higher concentration of body fat percentage in women than in men determines the higher females inner thermal resistance [62]. Since only 2 women participated in our study, we are unable to infer any differences with regard to the sex of the participants.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, Polidori et al [33] have shown that the body fat content affects the effectiveness of whole-body cryotherapy. They suggested that women are more sensitive to the extreme cold than men due to the greater inner thermal resistance connected with a higher concentration of body fat percentage.…”
Section: Results Shown Inmentioning
confidence: 99%
“…At the same time, the result obtained is significantly more than can be removed from a WBC device by using 2 kg of liquid nitrogen for one patient's cooling [6,10].…”
Section: Thermophysical Bases Of Achievement Of the Wbc Healthcare Efmentioning
confidence: 97%
“…And, judging by contemporary publications, this qualitative change had a negative impact on the healthcare effectiveness of the procedures, which until recently were successfully used to treat a number of severe diseases: rheumatoid arthritis, bronchial asthma, psoriasis, etc. [9,10].…”
Section: Introductionmentioning
confidence: 99%